2015
DOI: 10.1088/0957-4484/26/27/275605
|View full text |Cite
|
Sign up to set email alerts
|

Titanium-based silicide quantum dot superlattices for thermoelectrics applications

Abstract: Ti-based silicide quantum dot superlattices (QDSLs) are grown by reduced-pressure chemical vapor deposition. They are made of titanium-based silicide nanodots scattered in an n-doped SiGe matrix. This is the first time that such nanostructured materials have been grown in both monocrystalline and polycrystalline QDSLs. We studied their crystallographic structures and chemical properties, as well as the size and the density of the quantum dots. The thermoelectric properties of the QDSLs are measured and compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 15 publications
(26 reference statements)
1
11
0
Order By: Relevance
“…( d ) Seebeck coefficients of P-doped typical stacked structure (8-nm NDs/376-ML Si sample and 12-nm NDs/303-ML Si sample). Open square, circle, triangle and diamond marks indicate the reported values of bulk Si 9 45 , Si 0.7 Ge 0.3 45 and Si 0.87 Ge 0.13 thin film 46 for reference. The inset shows the thermal conductivities of non-doped (solid bar) and doped (open bar) nanoarchitectures.…”
Section: Figurementioning
confidence: 99%
“…( d ) Seebeck coefficients of P-doped typical stacked structure (8-nm NDs/376-ML Si sample and 12-nm NDs/303-ML Si sample). Open square, circle, triangle and diamond marks indicate the reported values of bulk Si 9 45 , Si 0.7 Ge 0.3 45 and Si 0.87 Ge 0.13 thin film 46 for reference. The inset shows the thermal conductivities of non-doped (solid bar) and doped (open bar) nanoarchitectures.…”
Section: Figurementioning
confidence: 99%
“…Moreover, another way to improve µTEGs performances would consist in using thermoelectric nanostructured materials instead of bulk SiGe layers. For example, our previous studies have already shown that the use of quantum dot superlattice (QDSL) based on TiSi2 nanoparticles inside a SiGe matrix improved the performances of micro-thermoelectric sensors (µTES) compared to the same µTES integrating bulk SiGe layers [16][17]. Combination of improved contact resistances with such high-performance nanostructured materials will enable these µTEGs to increase still more their performances.…”
Section: Discussionmentioning
confidence: 99%
“…Besides the apophysis heterostructure, Savelli et al 73) prepared an N-type Si/Ge SL within regular sphere Ti silicide QDs embedding, as shown in Fig. 7(b).…”
Section: Nsmentioning
confidence: 99%